The Intraplate Stress Field of West Africa - Jean‐Joel Legre; Yan Qin; Folarin Kolawole; Tolulope Olugboji (Geophysical Research Letters, 2024)
Abstract West Africa continues to host a growing number of low and intermediate‐magnitude earthquakes (M2‐5) along its passive margins, and its continental interior. Earthquake activity in these regions raises the need to comprehend the causes and the tectonic controls of the seismicity. Unfortunately, such studies are rare. Here, we apply single‐station inversion techniques to constrain fourteen focal mechanisms, computed after compiling a set of high‐quality waveforms. We describe the connection between seismicity, the contemporary stress field, anthropogenic activity and Holocene fault scarps in the region. Our results indicate transpressive stresses acting on the inherited brittle structures in the passive margins. We also observe a compressive regime in the intracontinental failed rifts. We attribute the seismicity to the reactivation of “weak” faults in the Neoproterozoic and Mesozoic failed rifts, the passive transform structures, and the intracratonic Precambrian brittle shear zones.